Impact of von Willebrand factor on coronary plaque burden in coronary artery disease patients treated with statins - Kato, Yuta (Medicine (Baltimore), 2018)
High von Willebrand factor (VWF) levels have been reported to be associated with an increased risk of cardiovascular events. However, the relationship between VWF levels and coronary atherosclerosis in patients with coronary artery disease (CAD) who have already received stain treatment is still unclear. We examined the association between VWF levels and coronary plaque as assessed by intravascular ultrasound (IVUS) in CAD patients treated with statins. Ninety-one CAD patients who underwent percutaneous coronary intervention under IVUS guidance, and who were already receiving statin treatment based on Japanese guidelines, were included. An IVUS examination was performed for the culprit lesion, and plasma VWF antigen levels were measured using enzyme-linked immuno sorbent assay. In all of the patients, the low-density lipoprotein cholesterol levels just before the IVUS examination were low (86 ± 26 mg/dL). The VWF levels were positively correlated with the plaque burden expressed as percent atheroma volume (PAV) (r = 0.39, P = .001), while there was no significant association between VWF and plaque composition. Multivariate stepwise regression analysis showed that higher VWF levels were independently associated with increased PAV (β=0.26, P = .01). In CAD patients who had already been treated with statins, higher VWF levels were associated with a higher coronary plaque burden, suggesting that a high VWF level may be a marker of the residual cardiovascular risk after statin treatment.